Prevalence of Transmitted Drug-Resistance Mutations and Polymorphisms in HIV-1 Reverse Transcriptase, Protease, and gp41 Sequences Among Recent Seroconverters in Southern Poland - Smoleń-Dzirba, Joanna (Med Sci Monit, 2017)
BACKGROUND: Monitoring of drug resistance-related mutations among patients with recent HIV-1 infection offers an opportunity to describe current patterns of transmitted drug resistance (TDR) mutations. MATERIAL/METHODS: Of 298 individuals newly diagnosed from March 2008 to February 2014 in southern Poland, 47 were deemed to have recent HIV-1 infection by the limiting antigen avidity immunoassay. Proviral DNA was amplified and sequenced in the reverse transcriptase, protease, and gp41 coding regions. Mutations were interpreted according to the Stanford Database algorithm and/or the International Antiviral Society USA guidelines. TDR mutations were defined according to the WHO surveillance list. RESULTS: Among 47 patients with recent HIV-1 infection only 1 (2%) had evidence of TDR mutation. No major resistance mutations were found, but the frequency of strains with ≥1 accessory resistance-associated mutations was high, at 98%. Accessory mutations were present in 11% of reverse transcriptase, 96% of protease, and 27% of gp41 sequences. Mean number of accessory resistance mutations in the reverse transcriptase and protease sequences was higher in viruses with no compensatory mutations in the gp41 HR2 domain than in strains with such mutations (p=0.031). CONCLUSIONS: Despite the low prevalence of strains with TDR mutations, the frequency of accessory mutations was considerable, which may reflect the history of drug pressure among transmitters or natural viral genetic diversity, and may be relevant for future clinical outcomes. The accumulation of the accessory resistance mutations within the pol gene may restrict the occurrence of compensatory mutations related to enfuvirtide resistance or vice versa.